State of nutrition and type of community as determinants of the performance of preschoolers on the Denver Developmental Screening Test. - Bacalzo, Fe T.
The study problem revolved around the questions: 1. How do rural and urban Filipino pre-schoolers differ in their responses to the Denver Developmental Screening Test? 2. How do nourished and malnourished Filipino pre-schoolers differ in their responses to the Denver Developmental Screening Test? In an effort to answer these questions the following hypotheses were posed: 1. Filipino pre-schoolers living in an urban area will perform better on the Denver Developmental Screening Test than those living in a rural area. 2. Nourished Filipino pre-schoolers will perform better on the Denver Developmental Screening Test than malnourished ones. 2 trained data collectors located the children in their homes by sampling every 5th household in the designated communities. The children were weighed by the use of a locally made bar scale called "espada" and the nutritional state of the child determined by the use of the FNRC Publication No. 137, a guide for the identification of degree of malnutrition by weight of Filipino children from 0 month to 102 months of age. The following are the findings in the 4 sectors or aspects of behavior as they relate to the hypotheses: 1. Urban vs. Rural Children: a. In a great majority (35 tasks or 67.31 ) of the 52 tasks considered for comparison, the urban children were more advanced than the rural children. Of these 35 tasks, 7 were performed significantly earlier by the urban subjects across the 4 aspects of behavioral measured. 2. Nourished vs. Malnourished Children: a. The nourished children generally showed a consistent tendency of obtaining the lower mean scores than the malnourished ones in the tasks that were tested on the 4 aspects of behavior. That is, almost all (50 or 96.15 ) of the 52 tasks that stood comparison, the nourished children were more advanced than the malnourished children. Of these 50 tasks, there were 9 tasks which the nourished children acchieved significantly earlier than the malnourished ones. In summary, the study findings were that: 1. While there was no strong pattern of significant differences between urban and rural subjects, the urban children showed a tendency to achieve the tasks earlier than the rural ones. 2. While there was no strong pattern of significant differences between nourished and malnourished children, the nourished children showed a consistent tendency to achieve the tasks earlier than the malnourished ones. 3. The language sector was where the most number of significantly different behavioral tasks occurred between the urban and rural children and between the nourished and malnourished ones. 4. As an incidental finding, the study children were found to be generally below the expectancies set by the Denver norms, particularly on the language and personal-social sectors.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Child development -- Testing; Education, Pre school. -- Philippines; Denver development screening test